Case report: Echocardiographic diagnosis of cardiac involvement caused by congenital generalized lipodystrophy in an infant - Zhou, Jie; Liu, Hanmin; Chen, Jiao; He, Xiaolan (Frontiers in Pediatrics, 2023)
We herein first report the use of conventional echocardiography combined with two-dimensional speckle-tracking to diagnose and monitor the changing process of cardiac involvement in an infant with congenital lipodystrophy. An 8-month-old girl was admitted to our hospital after first presenting at the age of 3 months with abnormal facial features that had been noticed within 4 weeks of birth. Echocardiography performed at the age of 3 months showed only slightly accelerated blood flow in the right ventricular outflow tract. At the age of 5 months, echocardiography showed myocardial hypertrophy; this finding combined with the physical characteristics and other examination results led to the consideration of congenital lipodystrophy. Genetic testing at the age of 9 months confirmed type 2 congenital lipodystrophy caused by BSCL2 gene mutation, and dietary modification was initiated. Conventional echocardiography performed at the ages of 5, 8, and 14 months showed no significant changes and a normal ejection fraction. However, two-dimensional speckle-tracking performed between the ages of 5 and 8 months showed cardiac systolic abnormalities that tended to improve after treatment. This case highlights the value of echocardiography in detecting structural and early functional cardiac changes in infants with congenital lipodystrophy.